CLINICAL SIGNIFICANCE OF PROCALCITONIN AND C-REACTIVE PROTEIN IN THE PREDICTION OF CARDIOVASCULAR COMPLICATIONS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Ahmed, Hanaa H; Shousha, Wafaa Gh; HATEM A EL-MEZAYEN; Emara, Ibrahim A; Hassan, Marwa E (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This work was delineated to assess procalcitonin (PCT) and C-reactive protein (CRP) as prognostic markers for cardiovascular complication in type 2 diabetic patients. Methods: Forty diabetic patients without cardiovascular disease (CVD), 40 diabetic patients with CVD, and 20 healthy control counterparts were participated in this study. Serum PCT and CRP levels were assayed and correlated with metabolic parameters. Receiver operating characteristic (ROC) curve analysis was done for each biochemical marker. Results: The mean level of PCT was 707.17Â±99.19 ng/l in diabetic patients versus 881.30Â±123.56 ng/l for the cardio-diabetic patients (p<0.0001). The mean value of CRP was 34.43Â±17.27 mg/l in diabetic patients versus 50.32Â±20.19 mg/l for the cardio-diabetic patients (p=0.0003). PCT levels were significantly amplified in the cardio-diabetic patients with increasing CRP, triglycerides (TG), fasting blood glucose (FBG), and cholesterol (p=0.004, 0.0005, 0.002, and 0.01, respectively). CRP levels were significantly enhanced in the cardio-diabetic patients with increasing TG, FBG, cholesterol, and microalbumin (p=0.002, 0.047, 0.003, and 0.001 respectively). ROC curve analysis for PCT and CRP revealed that the area under curve (AUC) was 0.878 and 0.727, respectively. These findings indicate the good validity of the above biomarkers especially PCT as a prognostic marker for cardiovascular complication in type 2 diabetic patients. Conclusion: This study evidences the usefulness of measuring serum levels of PCT and CRP in diagnosis of cardiovascular complication in type 2 diabetic patients.